GABA Receptor Agonists Protect From Excitotoxic Damage Induced by AMPA in Oligodendrocytes - Bayón-Cordero, Laura; Ochoa-Bueno, Blanca Isabel; Ruiz, Asier; Ozalla, Marina; Matute, Carlos; Sánchez-Gómez, María Victoria (Frontiers in Pharmacology, 2022)
Oligodendrocytes are the myelin forming cells of the central nervous system and their vulnerability to excitotoxicity induced by glutamate contributes to the pathogenesis of neurological disorders including brain ischemia and neurodegenerative diseases, such as multiple sclerosis. In addition to glutamate receptors, oligodendrocytes express GABA receptors (GABAR) that are involved in their survival and differentiation. The interaction between glutamate and GABAergic systems are well-documented in neurons, under both physiological and pathological conditions, but this potential cross-talk in oligodendrocytes has not been studied in depth yet. Here, we evaluated the protective effect, of GABAR agonists baclofen (GABAB) and muscimol (GABAA) against AMPA-induced excitotoxicity in cultured rat oligodendrocytes. First, we observed that both baclofen and muscimol reduced cell death and caspase-3 activation after AMPA insults, proving their oligoprotective potential. Interestingly, the analysis of cell-surface expression of calcium-impermeable GluR2 subunit in oligodendrocytes revealed that GABAergic agonists significantly reverted GluR2 internalization induced by AMPA. Furthermore, we detected that baclofen and muscimol also impaired AMPA-induced intracellular calcium increase and subsequent events as mitochondrial membrane potential alteration, ROS generation and calpain activation. However, AMPA-triggered activation of Src, Akt, JNK and CREB were not affected by baclofen or muscimol. Overall, our results suggest that GABAR activation initiates alternative molecular mechanisms that attenuate AMPA-mediated apoptotic excitotoxicity in oligodendrocytes by interfering with GluR subunits membrane expression and with calcium-dependent intracellular signaling pathways. Together, these findings provide evidence of the potential of GABAR agonists as oligodendroglial protectants in central nervous system disorders.